The Impact of Organizational Behavior, Trust, Commitment, and Job Motivation on Academic Staff and Employees - Humaida, Ibrahim Abdelrahim (Sultan Idris Journal of Psychology and Education, 2024)
The main objective of this research was to investigate the effect of the following factors affecting organizational development, such as organizational behavior, organizational trust, organizational commitment, and work/job motivation on academic staff and employees of Aljouf University- Faculty of sciences and arts. To fulfill this aim, the researcher employed causal research methodology, and the selected sample consisted of (70) academic staff and employees from both males and females, based on stratified random sampling technique. The instruments of data collection were scales for measuring: organizational behavior, trust, commitment, and work motivation. These scales were statistically manipulated to obtain their reliability and validity through Alpha Cronobach formula. The collected data representing the research’s hypotheses were also analyzed by using (SPSS), the following statistical tests were used to verify the hypotheses: Multiple regression, correlation coefficient, T-test, and ANOVA. The findings revealed that there was significant statistical difference on factors affecting academic staff and employees as human resources, also there was significant correlation and effect as well among above- mentioned factors. Conclusion: These four factors had a mutual impact and were considered as aspects of organizational development in both academic staff and employees